Application of the CIRC Model to Improve Learning Outcomes on Solar System Material in Class VII of SMPN 4 Tambang - Sa'adah, Y. Z.; Syahril, S.; Fakhruddin, Z. (Journal of Science Education Research, 2024)
The research aims to improve students' cognitive learning outcomes on Solar System material in the experimental class with the CIRC learning model and the control class with conventional learning. The research was conducted in May-June, the Even Semester of the 2022/2023 Academic Year at SMPN 4 Tambang, Tambang District, Kampar Regency, Riau Province. The population was all students of class VII which consisted of 10 classes and 315 students. The sample was selected using a purposive sampling technique. Class VII-B was selected as the experimental class and VII-C as the control class. The research was Quasi-Experimental with a posttest-only, Non-equivalent Control Design. The research showed that the posttest score in the experimental class was higher with a mean score of 77.9 in the category of good (B). Meanwhile, the control class obtained a score of 68.5 in the sufficient category (C). Inferential analysis with SPSS 25 was used to test the normality, homogeneity, and hypothesis. The normality and homogeneity tests showed the distribution of the both two classes were normal and homogeneous. Based on the hypothesis test with the Independent Sample T-test, a significance of 0.001 was obtained that there has been a significant increase in students' cognitive learning outcomes through the application of the CIRC model on the Solar System material in class VII of SMPN 4 Tambang.